2010
DOI: 10.1016/j.resuscitation.2009.09.015
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing the Arctic Sun to standard cooling for induction of hypothermia after cardiac arrest

Abstract: Context Hypothermia improves neurological outcome for comatose survivors of out-of-hospital cardiac arrest. Use of computer controlled high surface area devices for cooling may lead to faster cooling rates and potentially improve patient outcome. Objective To compare the effectiveness of surface cooling with the standard blankets and ice packs to the Arctic Sun, a mechanical device used for temperature management. Design, Setting, and Patients Multi-center randomized trial of hemodynamically stable comatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 18 publications
2
62
1
Order By: Relevance
“…[5][6][7][10][11][12][13] The primary end point evaluated in the 2 small, randomized, controlled trials comparing advanced surface cooling pads and endovascular or basic surface cooling was the proportion of patients reaching the TT and the efficacy evaluated by the neuron-specific enolase levels but not survival. 14,15 Finally, multiple available cooling devices can be used alone or in combination. 5,6 To date, human studies have not demonstrated a clear clinical impact of early cooling associated with a strict maintenance phase of TH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][10][11][12][13] The primary end point evaluated in the 2 small, randomized, controlled trials comparing advanced surface cooling pads and endovascular or basic surface cooling was the proportion of patients reaching the TT and the efficacy evaluated by the neuron-specific enolase levels but not survival. 14,15 Finally, multiple available cooling devices can be used alone or in combination. 5,6 To date, human studies have not demonstrated a clear clinical impact of early cooling associated with a strict maintenance phase of TH.…”
mentioning
confidence: 99%
“…5,6 To date, human studies have not demonstrated a clear clinical impact of early cooling associated with a strict maintenance phase of TH. 10,11,[14][15][16][17][18][19][20][21][22][23] Because endovascular cooling seems faster and more accurate than other available methods, 8,[11][12][13][14]24 the aim of the present study was to determine the clinical impact of advanced core endovascular cooling versus basic surface cooling after OHCA from a presumed cardiac cause in a multicenter, randomized, controlled trial.…”
mentioning
confidence: 99%
“…Nineteen studies indicated that cooling could be initiated safely with IV ice-cold fluids (30 mL/kg of saline 0.9% or Ringer's lactate) (LOE 3 748,749,825,831,833,837 ; LOE 4 779,780,782-785,810,836,838 -843 ). Six studies indicated that cooling with IV cold saline can be initiated in the prehospital phase (LOE 1 781,844 ; LOE 2 845 ; LOE 3 261,846 748,841,850,[853][854][855]. Seven studies documented the use of ice packs (sometimes combined with wet towels) alone to induce and maintain hypothermia (LOE 2 823 ; LOE 3 824,828,830 ; LOE 4 847,849,856 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…In a retrospective study by Merchant et al [71] of 32 patients in 3 large centers who underwent surface cooling using a mattress/blanket or ice bag, 63% of patients had temperature less than 32°C for more than 1 h. Temperature fluctuations also occurred throughout both the induction and ADH 0 xxxxx; IV 0 intravenous maintenance phases. This phenomenon has been consistently demonstrated in subsequent studies comparing different cooling methods [72][73][74]. Fans, washing the patient with alcohol baths, and ice immersions should not be used, as they are unpractical in the intensive care unit setting and ineffective for the maintenance and rewarming phases [3].…”
Section: Surface Coolingmentioning
confidence: 81%